Formation Mechanism and Mechanical Properties of Soil-Rock Mixture Containing Macropore - Feng Zhu; Wei Qian; Huilin Le; Haotian Fan; Wuchao Wang (Advances in Civil Engineering)
In southwestern China, soil-rock mixture containing macropore (SRMCM) is very common in large-scale accumulation slopes. The formation mechanism and mechanical parameters of SRMCM play an important role in slope stability. In this paper, we designed a new physical model test to study the formation mechanism of SRMCM. We analyzed different factors that influence the formation of SRMCM. The mechanical properties of SRMCM are obtained by direct shear test. New physical model test demonstrates the best slurry consistency (30%) and slope angle (35°∼45°) to form SRMCM. The results of direct shear test show that the strength parameters of SRMCM are high and it is influenced by the angle of macropore structure. When the angle of macropore structure increases, so does the cohesion of SRMCM. In this process, the internal friction angle does not change much.